Transparency in Ensuring Governance and Accountability of Non-Profit Institutions: Lessons from Malaysia and India - Tria Sasangka Putra; Bahrullah Akbar; Suwarno; Renny Friska; Dhanuskodi Rengasamy; Momin Noorjahan (APPTHI, 2024)
This research examines the transparency and governance aspects of foundations in Indonesia as nonprofit organizations, and compares them with foundation regulations in several countries to gain insight into their legal structures, obligations, and social responsibilities. The study addresses three key questions: first, how foundations are structured within Indonesia's legal framework, focusing on governance; and second, a comparative analysis of how Malaysia and India regulate foundations, their responsibilities, and operational frameworks. The research also evaluates how foundations can improve their societal contributions while ensuring transparency and accountability. Using a qualitative approach with a normative and comparative design, the study analyzes Indonesia's regulatory framework under Law No. 28/2004 and compares it with international practices to identify best practices. The findings reveal that Indonesian foundations must uphold transparency and accountability, including the obligation to produce annual reports that are auditable and subject to strict oversight to prevent fund misuse. The conclusion highlights that while regulations differ across countries, all emphasize the importance of transparency and accountability to ensure foundations operate effectively and contribute positively to society. Adhering to these principles is essential for the sustainability of foundations and enhancing their social impact.